Spatial Polarization in the System of International Tourism (London Journal of Research In Management & Business, 2024)
In tourism, the region has come to be seen as an important driving force, linking disparate segments of the industry and enabling the formation of destination networks (Milne 1998). This dependence is deepened by the fact that complex ecosystems, models of culture and economic identity, on which the development of tourism depends, are also regional in nature. Currently, community-oriented approaches occupy a prominent place in tourism development plans of various taximetric calibers around the world. Also, stakeholders are aware that local cooperation, trust and networking are important components of successful tourism development. Tourism is often seen as a key element that allows local communities that have suffered the devastating effects of economic restructuring to rebuild and strengthen their economic position in the regional and national economy. That is, it becomes expedient to talk about the transformation of the essence of city-forming factors that lead to the life sustainability of the settlement.
Keywords: Extreme weather events; Crop production risk; Econometric analysis; Management strategies; Adaptation measures; Food security; cruise tourism; global tourist destinations; international tourism; asymmetric smoothing of spatial polarization; tourism system; stakeholders.